Perfil del emprendedor en el sector artesanal de la ciudad de Cariamanga, cantón Calvas. Periodo de estudio abril-septiembre del 2022 - Tinizaray Castillo, Yessica Patricia (2023)
The present research is focused on the characterization of an entrepreneur’s profile in the craftmanship sector in the city of Cariamanga, which allowed to divulge the state of entrepreneurship in this city, in addition, a comparative analysis was made provincewide and nationwide. The methodology used for this study was descriptive in nature, as well as exploratory. In the same way, a historical documental method was used in order to gather all the information regarding research made provincewide and nationwide, the technique used was a questionnaire which was applied to the craftmanship population in the city of Cariamanga. The results obtained in this study showed that the female gender is the pioneer for entrepreneurship, it was also identified that the average age was 30 years with a high-school level of instruction, the economical sector in which craftspeople engage in, is the supply of services, the beauty industry, being the main source of income for these population. They create their own commerce out of necessity and the lack of jobs, the average income generated by the entrepreneurships are around $701 and $1100, it was also determined that the main difficulty to pursue self-work is due to bureaucracy and the administrative paperwork. Furthermore, it was determined that the source for funding to start their entrepreneurships were loans made to family and friends. The craftspeople of the sector have the next features, they are optimistic, they tend to see and evaluate things in a positive and favorable manner in order to make decisions, they have the capacity to solve issues, and they are passionate in the activities they enjoy.